The Effect of Team Game Tournament Method on Students’ Reading Comprehension at the Eleventh Grade of SMAN 1 Cihara in the Academic Year 2025/ 2026 - Muhamad Irwansyah; Ade Sudirman; Ridzki Elang Gumelar (CV. Kurnia Grup, 2026)
This research aims to investigate the effect of the Team Games Tournament (TGT) method on the reading comprehension skills of eleventh-grade students at SMAN 1 Cihara. The research method used was quantitative with a quasi-experimental design involving two groups, the experimental class and the control class. The population of this study consisted of 134 students from class XI of SMAN 1 Cihara, and the sample size was 64 students (32 students as the experimental class and 32 students as the control class). The research instrument used was a reading comprehension test (pre-test and post-test). The data were analyzed using SPSS version 25.0, including mean, standard deviation, and t-test. The results of the study indicate a significant effect of the TGT method on students' reading comprehension of narrative texts. This is supported by the higher average post-test score in the experimental class compared to the control class, and the t-test results which showed a significance value of 0.000 ≤ 0.05, meaning Ha is accepted and Ho is rejected. In conclusion, the TGT method is effective in improving reading comprehension skills for narrative texts among eleventh-grade students at SMAN 1 Cihara.